Symphony of the gut microbiota and endocannabinoidome: a molecular and functional perspective - Wang, Yang; Guo, Jing; Mao, Zhiqin; Chen, Ying (Frontiers in Cellular and Infection Microbiology, 2025)
This review examines the impact of interactions between the gut microbiota and the endocannabinoidome (eCBome) on health and disease, highlighting their significance for physiological and pathological processes. We identify key research gaps and challenges to advance the field. The review discusses the role of dietary patterns and physical activity in regulating these interactions. It also explores the complex nature of these interactions in conditions such as inflammatory bowel disease (IBD), depression, anxiety, Alzheimer’s disease (AD), and metabolic disorders. This analysis evaluates their contributions to disease onset and progression, and examines the molecular mechanisms and signaling pathways involved. From this, we provide forward-looking perspectives on future research directions, advocating for a more nuanced understanding of the gut microbiota–eCBome axis. We anticipate that future research will integrate gut microbiota–endocannabinoidome interactions into therapeutic strategies for a broad range of diseases.